PTU-062 Systematic review: the management of early pouch-related septic complications in ulcerative colitis. (8th June 2018) - Segal, Jonathan; Worley, Guy; Warusavitarne, Janindra; Clark, Susan; Faiz, Omar
Abstract : Introduction: It is well reported that ileoanal pouch-related septic complications (PRSC) increase the chance of pouch failure. There are a number of publications that describe the management of early PRSC in ulcerative colitis (UC) in small series. This article aims to systematically review and summarise the relevant contemporary data on this subject and provide an algorithm for the management of early PRSC. Method: A systematic review was undertaken in accordance with PRISMA guidelines. Studies published between 2000 and 2017 describing the clinical management of PRSC in patients with UC within 30 days of primary ileoanal pouch surgery were included. A qualitative analysis was undertaken due to the heterogeneity and quality of studies included. Results: 1157 abstracts and 266 full text articles were screened. Twelve studies were included for analysis involving a total of 207 patients. The studies described a range of techniques including image-guided, endoscopic, surgical and endocavitational vacuum methods. Based on the evidence from these studies, an algorithm was created to guide the management of early PRSC. Conclusion: Although the rate of successful salvage following early PRSC has improved over time there is a paucity of research correlating the method used with functional outcome. Short course Endo-SPONGE ® therapy with early surgical closure seems to offer increased chance of salvage. We present an algorithm for the management of early PRSC.